Units of rocket and artillery troops in the Orzysz garrison after 1945 – influence on the development and functioning of the city - Łach, Wiesław Bolesław (City and War, 2021)
The paper presents the development and functioning of the Orzysz as a town inextricably linked with the army from the mid-18th century. The Second World War, and especially the arrangements of the Allies in Tehran and Yalta, changed the face of the city. Orzysz found itself within the Polish borders to a great extent depopulated and destroyed. However, the former German military infrastructure remained intact in it, which became, from 1948, a place of dislocation of artillery units and, in the 1960s, rocket units of the Polish Army.The role of the military was important after the war from a demographic point of view. It became a guarantor of security and lost lands in the East for the people coming from central Poland to Masuria. The economic development of the Orzysz that took place at that time was conditioned by the needs of serving soldiers and professional staff. The members of the city’s civil life were also the families of the military staff living there. Military counterintelligence protection was also carried out in the garrison. It had a negative impact on the development of some economic branches of the city, especially tourism and culture. Over the years, this situation has reduced the city to a service role, to a greater extent in relation to the needs of the army and the environment associated with it.